2009
DOI: 10.1017/s0031182009005861
|View full text |Cite
|
Sign up to set email alerts
|

A new genotype of Trypanosoma cruzi associated with bats evidenced by phylogenetic analyses using SSU rDNA, cytochrome b and Histone H2B genes and genotyping based on ITS1 rDNA

Abstract: We characterized 15 Trypanosoma cruzi isolates from bats captured in the Amazon, Central and Southeast Brazilian regions. Phylogenetic relationships among T. cruzi lineages using SSU rDNA, cytochrome b, and Histone H2B genes positioned all Amazonian isolates into T. cruzi I (TCI). However, bat isolates from the other regions, which had been genotyped as T. cruzi II (TC II) by the traditional genotyping method based on mini-exon gene employed in this study, were not nested within any of the previously defined T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
209
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(242 citation statements)
references
References 40 publications
19
209
0
14
Order By: Relevance
“…In the present study, TcI was identified in a single isolate (CT-IOC 541) from a chronic patient with the indeterminate form, who originated from the Paraíba State (Northeastern Brazil). A sequencing assay followed by BLAST analysis displayed its higher genetic similarity (99%) with several TcI strains, first Sylvio X10, a stock originally of a human case from the Pará State (Northern Brazil), besides a Tcbat stock 16,17 . The genotype TcI had already been found in two patients from the Paraíba State by Barnabé et al 37 , and in three individuals from another close State (Rio Grande do Norte) by Câmara et al 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, TcI was identified in a single isolate (CT-IOC 541) from a chronic patient with the indeterminate form, who originated from the Paraíba State (Northeastern Brazil). A sequencing assay followed by BLAST analysis displayed its higher genetic similarity (99%) with several TcI strains, first Sylvio X10, a stock originally of a human case from the Pará State (Northern Brazil), besides a Tcbat stock 16,17 . The genotype TcI had already been found in two patients from the Paraíba State by Barnabé et al 37 , and in three individuals from another close State (Rio Grande do Norte) by Câmara et al 38 .…”
Section: Discussionmentioning
confidence: 99%
“…According to consensus among specialists, the main T. cruzi genetic types were correlated to those six DTUs, and they were renamed Trypanosoma cruzi I-VI (TcI-TcVI) 7,14,15 . Subsequently, a new genotype closely related to TcI was described in Brazilian bats 16 and named Tcbat or TcVII, although without consensus regarding its DTU assignment 8,17,18 . In Brazil, TcI (formerly Z1) is widely distributed among mammalian hosts within the wild cycle, mainly the common opossum, Didelphis marsupialis, but it can also be found in human acute infections and more rarely in chronic patients 6,7,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that such a pattern was 'self-evident' (Ramírez and Llevellyn, 2015) is easy when arriving long after the battle and amounts to saying that the results of any phylogenetic analysis are self-evident. With such a view, the discovery of the newly described Trypanosoma cruzi near-clades Tc-Bat (Lima et al, 2015;Marcili et al, 2009;Pinto et al, 2012Pinto et al, , 2016 was self-evident, as was the description of the lesser near-clades within the T. cruzi near-clade TCI . Evidencing near-clades is all the less self-evident, since even the widely accepted number of near-clades within the thoroughly studied species T. cruzi (Brisse et al, 2000;Zingales et al, 2012) still is under debate (Barnabé et al, 2016).…”
Section: Strong Phylogenetic Signal Evidencing the Occurrence Of Stabmentioning
confidence: 99%
“…DNA samples were subjected to the conventional polymerase chain reaction (PCR) for trypanosome barcoding on a fragment of approximately 900 base pairs (bp) of the V7V8 SSU rDNA [18,20] and gGAPDH gene [21]. PCR products of the expected size were purified and sequenced in an automated sequencer (ABI Prism 310).…”
Section: Molecular and Phylogenetic Analysismentioning
confidence: 99%